Integration of social media into HRM practices: a bibliometric overview - Md Sajjad Hosain (PSU Research Review, 2023)
Purpose – This paper aims to critically discuss the mounting role of social media (SM) or social networking sites (SNSs) on various human resource management (HRM) practices. Design/methodology/approach – The paper is based on 87 published papers collected from the Web of Science Database particularly from 2010 to 2020 (up to June) using VOSviewer software. After reviewing those paper contents, the author briefly highlighted the findings. Findings – According to most of the previous studies, the utilization of SM information for various HRM practices is rising although such utilization is mostly limited to talent search and recruitment & selection at present. Further, it was found that Facebook and LinkedIn are the two most accepted sites among the hiring professionals where the first one mostly provides behavioral information and the second one provides job-related information. Finally, it was revealed that organizations can develop a strong corporate branding through the presence in SM. Research limitations/implications – This review paper is expected to motivate further research initiatives regarding the role of social media into different HRM practices. Practical implications – The author expects that based on the findings, the organizational policymakers can get some practical guidelines regarding the efficient utilization of such a platform. Originality/value – Social media is a powerful platform for flourishing business entities, promoting products, branding, talent search and so many more purposes. An organization can well promote its existence through this popular platform. In particular, the media can be a well-established platform for searching competent employees and creating employer branding. Therefore, more and more research studies should be carried out focusing on this recent issue. This review paper can be a base for the upcoming researchers as it has accumulated the previous literature and their findings.